Rebel McKenzie - Ransom, Candice F. 1952- (New York : Disney/Hyperion Books, 2012)
When feisty twelve-year-old Rebel McKenzie, an aspiring paleontologist, goes to spend the summer taking care of her older sister's seven-year-old son at the mobile home park in Frog Level, Virginia, she never expects to enter a beauty pageant or meet a hand model.
Keywords: Country life -- Juvenile fiction -- Virginia; Nephews -- Juvenile fiction; Loss (Psychology) -- Juvenile fiction; Beauty contests -- Juvenile fiction; Trailer camps -- Juvenile fiction; Country life -- Fiction -- Virginia; Nephews -- Fiction; Loss (Psychology) -- Fiction; Beauty contests -- Fiction; Trailer camps -- Fiction; Virginia -- Juvenile fiction; Virginia -- Fiction